CHALLENGE OF ARBITRATORS IN INTERNATIONAL INVESTMENT ARBITRATION - Daujotas, Rimantas (Teisė, 2015)
This article discussed what is the standard of successful challenge procedure of ICSID arbitrators and whether the cause of a small number of successful challenges is due to the provisions of the Convention or the reluctance of arbitrators to apply external standards, such as Guidelines on Conflicts of Interest in International Arbitration (IBA Guidelines). Author analyzed the interpretation of ICSID Convention as well as practice of challenge procedures in ICSID practice. It was argued that the challenge of an arbitrator in ICSID arbitration, although possible, is rarely successful. Article 57 of the ICSID Convention provides that arbitrators may be disqualified on the basis of any fact indicating a manifest lack of the qualities required by paragraph (1) of Article 14 (i.e., the failure to be a person of high moral character and recognized competence in the fields of law, commerce, industry or finance, who may be relied upon to exercise independent judgment). Thus, a party submitting the challenge must establish the facts which would prove that “there is a real risk of lack of impartiality based upon those facts (and not on any mere speculation or interference)”. It was found that that challenges tend to rest on three main grounds: relationships with parties, relationships with parties’ counsel or law firms, involvement in other arbitrations raising similar issues. Therefore, it was observed that although grounds of challenge are quite similar in practice, however, the outcome of challenges of ICSID arbitrators is quite conflicting. Likewise situations provide different results – either the arbitrators resign themselves or the challenge is rejected by the rest of the members of the tribunal. Thus, it is difficult to draw clear boundaries of a successful challenge of the ICSID arbitrator. The author also found that the practice of an ICSID arbitrator challenge, although quite narrow, provides that much of the successful challenge procedure depends not on the rules or provisions applicable, but more facts of each case and of the decision of arbitrators themselves.